2014
DOI: 10.3171/2014.7.jns132661
|View full text |Cite
|
Sign up to set email alerts
|

Results of immunohistochemical staining for cell cycle regulators predict the recurrence of atypical meningiomas

Abstract: Object The aim of this study was to evaluate the role of certain cell-cycle regulatory proteins in the recurrence of atypical meningiomas. These proteins were analyzed with immunohistochemical staining to identify predisposing factors for the recurrence of atypical meningiomas. Methods The authors retrospectively reviewed the medical records of patients with atypical meningiomas diagnosed in the period from January 2000 to June 2012 at the Department of Neurosurgery at Samsung Changwon Hospital and Dong-A Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 50 publications
4
37
0
Order By: Relevance
“…The mean follow-up time in 80 patients was 4 years (range 6 months to 10.5 years). The results are similar to data previously published in the literature describing from 26 ( 17 ) to 120 ( 23 ) patients followed for a period of 8 months ( 24 ) to 21 years ( 23 ).…”
Section: Discussionsupporting
confidence: 90%
“…The mean follow-up time in 80 patients was 4 years (range 6 months to 10.5 years). The results are similar to data previously published in the literature describing from 26 ( 17 ) to 120 ( 23 ) patients followed for a period of 8 months ( 24 ) to 21 years ( 23 ).…”
Section: Discussionsupporting
confidence: 90%
“…Cyclin D1 and CDK4, cell cycle proteins, can form a complex known as Cyclin D1/CDK4 to drive cells through the cell cycle G1/S checkpoint to initiate activation (Kim et al, 2014;Liu et al, 2018). We found that curcumin exposure increased the expression of CDK4 and Cyclin D1 protein significantly, and the expression of CDK4 and Cyclin D1 induced by curcumin was relieved by DAPT treatment, which was consistent with the result of BrdU/Nestin, Notch1, and Hes1 protein.…”
Section: Figsupporting
confidence: 79%
“…As regards the extent of resection, which is a significant independent predictive factor of recurrence in atypical meningiomas as well as in meningiomas overall, many authors have reported similar results. As published previously (the data was not presented in this article), the results in the present study-those obtained through Kaplan-Meier survival analysis and the Cox proportionalhazards regression model-correspond well with these findings, suggesting that the most important factor in determining the likelihood of meningioma recurrence is the extent of tumor resection [51]. However, in this study, postoperative radiotherapy was not an independent factor predicting the recurrence of atypical meningiomas in the multivariate analysis (Cox proportional-hazards regression model), and it showed only a tendency to predict a recurrence (p=0.058) [51].…”
Section: Journal Of Clinical Epigeneticssupporting
confidence: 80%